2018
DOI: 10.1007/s10144-018-0606-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficient single‐survey estimation of carnivore density using fecal DNA and spatial capture‐recapture: a bobcat case study

Abstract: Population density estimates are necessary to inform management and conservation, yet are difficult to obtain for cryptic species such as carnivores, and often require intensive sampling. We implemented a single‐survey, closed session, scat sampling protocol to estimate bobcat density using fecal DNA and spatial capture‐recapture at two sites over five sessions in Virginia, USA. We employed a Poisson encounter model to allow for multiple detections on scat transect segments over a single collection interval, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 54 publications
1
42
0
Order By: Relevance
“…and cougars ( Puma concolor ) remain extirpated from ecosystems in the Appalachian Mountains, leaving bobcats as an apex predator in the region, along with black bears ( Ursus americanus ) and coyotes ( Canis latrans ) [8]. Within this guild, bobcats are the only obligate carnivore, can occur at population densities approximately twice that of coyotes [9,10], and consume a diversity of taxa [8]. Thus, bobcats hold potential to influence populations of both prey and competitors, and understanding the spatial ecology of bobcats may be important to predicting spatial variation in top-down forces in these systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and cougars ( Puma concolor ) remain extirpated from ecosystems in the Appalachian Mountains, leaving bobcats as an apex predator in the region, along with black bears ( Ursus americanus ) and coyotes ( Canis latrans ) [8]. Within this guild, bobcats are the only obligate carnivore, can occur at population densities approximately twice that of coyotes [9,10], and consume a diversity of taxa [8]. Thus, bobcats hold potential to influence populations of both prey and competitors, and understanding the spatial ecology of bobcats may be important to predicting spatial variation in top-down forces in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Existing information on bobcat spatial ecology in the region comes from studies conducted during the 1980s in Tennessee and Kentucky, both of which had sporadic monitoring associated with use of VHF telemetry and did not examine habitat selection [32,33]. Existing information on bobcat population and trophic ecology in Virginia comes from noninvasive genetic sampling and examination of stomach contents [9,10,34]. In the eastern portion of their range, most research into bobcat spatial ecology has been conducted in the Southeast and Northeast, yet these areas represent considerably different ecosystems than the central Appalachian Mountains.…”
Section: Introductionmentioning
confidence: 99%
“…In Illinois, USA, forested landscapes have been reduced by 64% and currently characterized by young (<61‐year‐old) forests limited to the southern and western regions of the state (Crocker ). For these reasons, sound estimates of abundance are needed for monitoring the status of bobcat populations, detecting temporal changes in population trends, and promoting appropriate management decisions (Morin et al ).…”
mentioning
confidence: 99%
“…Despite widespread distribution of bobcats throughout North America, estimates of abundance are limited and often constrained by the inability to make direct comparisons with previous studies because of nonstandardized methodologies and associated variability in sources of sampling bias (Thornton and Pekins , Morin et al ). Nevertheless, early attempts to estimate density of bobcats have relied primarily on techniques that lack measures of accuracy and precision, including indices of relative abundance such as trap‐nights per individual captured (Wood and Odum , Jenkins et al ), harvest (O’Brian and Boudreau ), snow‐tracking (Golden ), mail questionnaires (Anderson ), and scent‐station surveys (Linhart and Knowlton , Johnson and Pelton , Conner et al ); previous studies have identified sex‐ and age‐specific biases in each of these methods (Diefenbach et al ).…”
mentioning
confidence: 99%
“…SCR models are well-suited for noninvasive genetic sampling in which individuals are uniquely identified, typically using DNA from feces or hair samples, to produce fully-observable encounter histories (Gardner et al 2009, Kery et al 2011, Morin et al 2016, 2018). Scat-detection dogs in particular have become a common tool to efficiently collect feces on large landscapes within a narrow time window to ensure demographic closure even for species that occur at low densities (Wasser et al 2004, 2011).…”
Section: Introductionmentioning
confidence: 99%